Text Mining of Economic Factors Causing Divorce: A Case Study of Decisions From the Klaten Religious Court - Bagus Fadilah Zikri; Fahmi Ali Hudaefi (proceedings.icesy, 2026)
This study analyzes economic factors in divorce cases at the Klaten Religious Court, Central Java, Indonesia. Employing a mixed-methods approach, the study examines 81 divorce verdicts selected via purposive sampling (from 405 economically motivated cases between January and August 2025). The data were analyzed using text mining techniques including word frequency analysis, Latent Dirichlet Allocation (LDA) topic modeling, and network visualization as well as inductive qualitative reasoning. The results identify three dominant typologies: the inability to fulfill financial support obligations, employment instability (unemployment or bankruptcy), and destructive economic behaviors, specifically online gambling addiction and illegal online loans. These findings indicate that digital economic vulnerability has emerged as a critical driver of marital dissolution, shifting traditionally homogenous legal narratives. The study recommends differentiated policy interventions, specifically behavioral rehabilitation programs for addiction cases and structural economic policies for systemic poverty as a foundation for evidence-based socio-legal reforms.